2021
DOI: 10.1186/s13643-021-01620-w
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect evidence of efficacy and safety of rapid exercise tests for exertional desaturation in Covid-19: a rapid systematic review

Abstract: Background Even when resting pulse oximetry is normal in the patient with acute Covid-19, hypoxia can manifest on exertion. We summarise the literature on the performance of different rapid tests for exertional desaturation and draw on this evidence base to provide guidance in the context of acute Covid-19. Main research questions What exercise tests have been used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…A post-COVID-19 functional status scale has been developed pragmatically but not formally validated [ 124 ]. Pulse oximeters may be extremely useful for assessing and monitoring respiratory symptoms after COVID-19 with no evidence that their home use leads to increased anxiety [ 125 ]. Close to 50% of COVID-19 patients who required hospital admission had hypoxia on exertion without subjective dyspnea at the time of discharge.…”
Section: A Follow-up Clinical Pathway For Pasc Patients With Long-term Neurological Manifestationsmentioning
confidence: 99%
“…A post-COVID-19 functional status scale has been developed pragmatically but not formally validated [ 124 ]. Pulse oximeters may be extremely useful for assessing and monitoring respiratory symptoms after COVID-19 with no evidence that their home use leads to increased anxiety [ 125 ]. Close to 50% of COVID-19 patients who required hospital admission had hypoxia on exertion without subjective dyspnea at the time of discharge.…”
Section: A Follow-up Clinical Pathway For Pasc Patients With Long-term Neurological Manifestationsmentioning
confidence: 99%
“…As highlighted in a recent systematic review, there remains little published data on EIH and COVID-19, and none of its role within the ED. 7 One recent paper has highlighted a modest association of EIH with critical care needs. 9 Due to public health interventions and falling case numbers at the time of this study, this was not powered to explore concomitant associations.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] A recent systematic review identified only two studies which have investigated EIH in COVID-19. 7 One study focused on its use at discharge and identification of pulmonary embolism. 8 Another retrospective study of admissions to 70 UK hospitals assessed the association between EIH and subsequent need for mechanical ventilation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the distance that they were able to walk off oxygen, the activities they were able to do, and the length of time that they felt comfortable off oxygen, were slightly more subjective but also useful signs of recovery. The '40 step test' [2,3] was introduced as a means of standardising the level of exertion for the purposes of comparison, even though it has not been validated. • After 2 weeks of static indicators, having excluded other causes, we accepted a new baseline of oxygen saturation, even <90%, and sent the patient home.…”
Section: Case Seriesmentioning
confidence: 99%